2011
DOI: 10.1021/ja109131w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Au102(p-MBA)44Nanoparticles

Abstract: The synthesis of Au(102)(p-MBA)(44) nanoparticles on a preparative scale in high yield is described. Various analytical methods are shown to give results consistent with the composition and known structure of the particles, showing the preparation is essentially homogeneous, and attesting to the validity of the methods as well. Derivatization of the particles with proteins and DNA is demonstrated, and conditions are described for imaging individual particles by cryo-EM at low electron dose, close to focus, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
257
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(282 citation statements)
references
References 26 publications
16
257
0
Order By: Relevance
“…11 Following this seminal work, various methods have been developed so far to synthesize monodisperse gold nanocluster of definite particle sizes by controlling the initial reaction conditions such as the thiol-to-gold ion ratio, reducing agents, temperature and also by modifying the post-synthesis purification processes. Several well defined nanoclusters have been synthesized so far such as Au 20 (SR) 16 , Au 25 (SR) 18 , Au 38 (SR) 24 , Au 102 (SR) 44 , and Au 144 (SR) 60 . [12][13][14][15][16][17] Among all these thiolate protected gold nanocluster, Au 25 (SR) 18 and Au 144 (SR) 60 are most widely studied due to their higher stability in comparison to other thiolated gold nanocluster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Following this seminal work, various methods have been developed so far to synthesize monodisperse gold nanocluster of definite particle sizes by controlling the initial reaction conditions such as the thiol-to-gold ion ratio, reducing agents, temperature and also by modifying the post-synthesis purification processes. Several well defined nanoclusters have been synthesized so far such as Au 20 (SR) 16 , Au 25 (SR) 18 , Au 38 (SR) 24 , Au 102 (SR) 44 , and Au 144 (SR) 60 . [12][13][14][15][16][17] Among all these thiolate protected gold nanocluster, Au 25 (SR) 18 and Au 144 (SR) 60 are most widely studied due to their higher stability in comparison to other thiolated gold nanocluster.…”
Section: Introductionmentioning
confidence: 99%
“…Several well defined nanoclusters have been synthesized so far such as Au 20 (SR) 16 , Au 25 (SR) 18 , Au 38 (SR) 24 , Au 102 (SR) 44 , and Au 144 (SR) 60 . [12][13][14][15][16][17] Among all these thiolate protected gold nanocluster, Au 25 (SR) 18 and Au 144 (SR) 60 are most widely studied due to their higher stability in comparison to other thiolated gold nanocluster. The X-ray crystal structure of the Au 25 (SCH 2 CH 2 Ph) 18 nanocluster was also recently determined in both anionic and neutral forms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Gold has been studied most extensively, and it has been interesting to observe that the results can be separated into two categories: (1) small nanocrystals, better termed clusters of gold atoms, such as Au 24 , 13 Au 25 , [14][15][16][17][18] Au 38 , 11,19 Au 102 , 20 Au 130 , 21 Au 144 , 22 Au 225 , 23 and a few others; (2) gold nanoparticles of 3 -5 nm (1000 to 4000 atoms) [1][2][3][4][5] and sometimes 9 -10 nm. 24 For both categories it has been shown that there are clearly numerous examples of size focusing under apparent thermodynamic control.…”
Section: Introductionmentioning
confidence: 99%
“…After those pioneering studies, extensive research on NPs characterization by MALDI has been reported [66][67][68][69]. Such MALDI-MS investigations have demonstrated this MS-based technique capabilities for the characterization of a broad range of AuNPs (with cores ranging between 16-144 atoms of gold), and providing enough resolution to be able to discriminate between Au38 and Au40 clusters.…”
Section: Matrix-assisted Laser Desorption/ionizationmentioning
confidence: 99%
“…As an example, both techniques have been simultaneously used during the characterization of the products resulting from the synthesis of Au102(p-MBA)44 NPs [69]. Information about molecular weight (22 kDa) is given by MALDI-MS whereas ESI-MS is used to determine the chemical formulas and charge states of thiolate-protected gold clusters.…”
Section: Electrospray Ionizationmentioning
confidence: 99%